Gender, population dynamics, and growth: The interplay between economic structure and demographics. Issue 1 (2nd October 2018) - Heintz, James
Abstract: This article presents an approach to modeling long-run growth in which endogenous population dynamics affect an economy's growth path. It links economic structure, captured by variations in aggregate returns to scale, to macroeconomic dynamics, in which changes in the costs of reproducing the population affect patterns of growth. Within the model, women are assumed to make fertility decisions that are affected by preferences, norms, and the expected costs of raising children. Unlike most growth models with endogenous fertility, it allows for negative population growth. Specifically, economies may gravitate toward a situation of below-replacement fertility and stagnant growth of per capita income, whereas others may become stuck in an unstable, high-fertility equilibrium. The article considers policy alternatives, including gender-equitable family policies and more open immigration, to address demographic challenges.